Social practices of flood (risk) management – a visual geographic approach to the analysis of social practices in an empirical case in Chiapas, Mexico - Stephan, Christiane (ERDKUNDE, 2018)
When discussion of risks takes place, whether in political debates or in scientific discourses, flood-related hazards are among the most frequently mentioned events in many world regions. Scientific explanations of the risk present in any geographical region are generally based on the hydro-physical process of flooding, and the specific vulnerabilities of the local population in respect of this process. This paper follows a different pathway, arguing that this perspective is limited in explaining the existence of specific patterns of socio-spatial activity which lead to inequalities in flood risk management. Using social practice theory and applying the concept of riskscapes allows for a more differentiated perspective on the presence and evolution of risks in spatial entities. By using the specific conceptual delineation of social practices elaborated by social theorist Theodore Schatzki the focus is put on materially and spatially relevant performances that are involved in social constructions of risk. Moreover, a specific empirical method of in-depth research into socially and spatially relevant practices is presented. This visual geographic approach, developed in empirical research in Mexico as part of a recently finalised dissertation project, involves a participatory photography workshop as a method to trigger reflection on social practices, and analyses the photographs produced in order to identify relevant material aspects of social practices relating to flood management. The empirical findings present specific social flood management practices along the river Usumacinta in Chiapas. It is shown that participatory visual methods contribute to the identification of relevant social dynamics of flood management, and that they allow in-depth analysis of the interlinkages between different social practices, identifying synergies and conflicts between practices related to flood management. The tool developed based on the riskscapes concept is promoted here as a relevant step towards more thorough analysis of social practices, with the aim of identifying politically relevant inequalities in processes of flood management in the south of Mexico, and hopefully beyond.